2016
DOI: 10.1002/ajmg.a.37930
|View full text |Cite
|
Sign up to set email alerts
|

Growth pattern in Kabuki syndrome with a KMT2D mutation

Abstract: Kabuki syndrome is a multiple congenital malformation syndrome with a spectrum of clinical features including short stature. Since there is no growth data on Kabuki syndrome patients with a proven KMT2D gene mutation, further research on growth and growth patterns is indicated. Data for this growth study on subjects with Kabuki syndrome were collected from referring clinicians. Subjects were eligible for inclusion in the study if the following criteria were met: a genetically confirmed diagnosis of Kabuki synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
(31 reference statements)
5
23
0
1
Order By: Relevance
“…In this series, 39% of KS1 individuals showed postnatal growth retardation, with H < −2 SD (35 of 89:17 of 51 males and 18 of 38 females) (Table S7). Our data are consistent with the literature (−2 SD in 35–71% individuals) (Armstrong et al, ; Matsumoto & Niikawa, ; Schott et al, ; Schrander‐Stumpel et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In this series, 39% of KS1 individuals showed postnatal growth retardation, with H < −2 SD (35 of 89:17 of 51 males and 18 of 38 females) (Table S7). Our data are consistent with the literature (−2 SD in 35–71% individuals) (Armstrong et al, ; Matsumoto & Niikawa, ; Schott et al, ; Schrander‐Stumpel et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study, we confirmed this physical manifestation in the Dutch and Belgian KS population [5], where the mean adult height in men was 162 cm and that for women 147.7 cm. The cause of this growth retardation is unknown, but there are several reports of growth hormone (GH) deficiency in the literature [6-9].…”
Section: Introductionsupporting
confidence: 62%
“…We previously described the growth pattern among Dutch and Belgian KS subjects with a KMT2D mutation [5]. All of them showed a reduction in growth during childhood, but a genotype-phenotype correlation was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of KMT2D gene function on chromosome 12 in humans has been described as responsible for Kabuki syndrome (KS), a rare autosomal dominant congenital disorder characterized by multiple anomalies involving the development and function of various organ systems . Major clinical components include typical facial dysmorphic features, postnatal growth retardation, hypotonia, skeletal abnormalities, dermatoglyphic changes and mild to moderate intellectual disability …”
Section: Introductionmentioning
confidence: 99%
“…12 Major clinical components include typical facial dysmorphic features, postnatal growth retardation, hypotonia, skeletal abnormalities, dermatoglyphic changes and mild to moderate intellectual disability. [13][14][15] This study established a strategic exome sequencing methodology to select potential causative mutations in an ENU-induced mutant with a BALB/cJ background. Then, after the identification of a single missense mutation in the Kmt2d candidate gene, we used behavioral tests to evaluate the bapa mutant and its potential as a novel mouse model to study brain-associated diseases such as KS.…”
Section: Introductionmentioning
confidence: 99%